Obraz czy figura? Uwagi o ołtarzu św. Stanisława Kostki w rzymskim kościele Sant’ Andrea al. Quirinale - Dzik, Janina (TECHNE. Seria Nowa, 2018)
The Roman memorial altar devoted to Stanislaus Kostka (1550–1568), a Polish saint of international importance, was an exceptional example of how a modern reredos was constructed in the era of the counterreformation. Located in the Jesuit novitiate, the Church of Sant’Andrea al Quirinale is part of an unusual facility for the veneration of Kostka, which focuses on two separate entities – the chapel of the novitiate church and the monastic cell. The paper attempts to determine the role of the altar (which has undergone modifications and exhibits Kostka’s effigy) as the most significant object of worship and liturgy. Three phases can be distinguished: 1) the first reredos, resembling an altar over the saint’s grave, was constructed in about 1605 within the novitiate church of Sant’Andrea in Monte Cavallo, and rebuilt by the Jesuit Giovanni Tristano as a setting for Kostka’s image, 2) a monumental altar in the oval space of the new novitiate church, designed by Gian Lorenzo Bernini (1658–1661), who wished to have a new and suitable altar painting, as evidenced by Ciro Ferri’s design and several variants prepared by Carlo Maratta, 3) the modification of the altar related to the planned canonization – and following the rejection of the 1713 conception by the sculptor Legros – involved placing a figure of the dying Kostka and providing it with the backdrop of an altar painting. As we learn from archival sources, a prerequisite for an artwork to be accepted and exhibited was that it should inspire piety and eschew ‘devotionally ineffective’ elements. This was because a painting was believed to play an important mediatory role, since it was more effective than a sculpture in arousing religious emotions. Kostka’s charismatic piousness and his mystical sensations, regularly emphasised in the iconography, were a perfect example of deep emotional experience. According to Federico Borromeo, ‘by nature and instinct’, people can precisely sense the emotions of those they observe and can tune into their feelings. It was the Jesuits’ intention for the altar to fulfil its medial devotional efficiency, through its artistic power.